A Development of Green Building in Malaysia: A Challenge to Sports Center - Shahron, Syairah Aimi; Abdullah, Rohani; Musa, Suria (CENTRAL ASIA AND THE CAUCASUS, 2021)
Considering the sports center consume much nonrenewable energy, this study focuses on environmentally friendly sports centers or green sports centers. More specifically, this paper focus on green buildings and sports center in Malaysia since Malaysia is still far behind in environmental management compared to developed countries. Thus, this paper sought to identify challenges and obstacles the sports center faces in implementing green practices or facilities. The data were collected through combinations of literature reviews related to green sports center, green building in Malaysia, and benefits and challenges faced by the construction industry, specifically the sports center. Results revealed that multiple challenges prevent sports center from adopting environmentally friendly facilities: higher cost to build, psychological obstacles from citizens, apathy and negative attitudes towards eco- friendly products and practices, lack of financial supports, and insufficient experts and human power. This paper suggests that to successfully building a green sports center, these challenges and obstacles need to be resolved. Besides that, this paper also discussed the benefits of the green sports center.